HOW TO ORGANIZE THE LESSON EFFECTIVELY - Akhunkhodjaeva N.T.; Rozmetova Z.Sh. (PEDAGOGS, 2024)
Abstract. The article depicts the objectives for conducting an effective and exciting lesson for students. How to use unusual, interesting tasks in order to involve students to participate actively and keep their attention at the lessons.